A research on improving the precision of laser tracker in alignment based on Pareto improvement principle - Zhong, Wen; Cheng, Wenjie; Gao, Tianyu; Zhang, Xin; Mao, Jianjun; Qi, Zhijun; Liu, Zengquan; Yu, Hang; Liu, Ming; Wang, Wei (Review of scientific instruments, 2024)
The accuracy of laser trackers in large-scale dimensional metrology is subject to various influencing factors, with instrument positioning being a primary source of error. To address this, a multi-objective optimization algorithm, grounded in the Pareto improvement principle, is proposed. This algorithm is designed to optimize instrument placement, thereby minimizing measurement errors and enhancing the algorithm's efficacy in error reduction. Thereby, this article proved that positioning the laser tracker consistently on one side of the measurement area and aligning its height with the measuring points can effectively reduce the uncertainty of control point errors by up to 50%.